Sentencing Disparity in Judicial Decisions on the Criminal Act of Disseminating Pornographic Content - Nur Septiana Amanda; Yuliana Yuli Wahyuningsih (Lambung Mangkurat Law Journal, 2026)
This study examines the sentencing disparity in judicial decisions concerning the dissemination of pornographic content, which demonstrates inconsistency in the application of the law. The Decision of the Palu District Court No. 352/Pid.Sus/2024/PN Pal imposed a heavier sentence for an act involving a limited scale of dissemination, whereas the Decision of the Pekanbaru District Court No. 579/Pid.Sus/2025/PN Pbr imposed a lighter sentence despite the case involving a more serious scale. This normative legal research employs statutory, case, and conceptual approaches. The findings indicate that the disparity is influenced by juridical factors, including the legal system, the formulation of legislation, evidentiary processes in court, and the absence of sentencing guidelines, as well as non-juridical factors in the form of judges’ characteristics, differences in assessing aggravating and mitigating factors, the offender’s motive, and the impact on the victim. The presence of disparity cannot be eliminated outright but can be minimised through the implementation of the sentencing guidelines under Article 54 Paragraph (1) of the New Criminal Code (KUHP), the issuance of a special Supreme Court Regulation (PERMA) on cybercrime with measurable parameters, the strengthening of PERMA Number 3 of 2017 regarding gender perspective and restorative justice, and the enhancement of law enforcement officers’ capacity to understand the characteristics of digital crime